Digital switching system / Mazni Omar and Fariza Ishak - Omar, Mazni; Ishak, Fariza (2001)
Our project entitled digital switching system. It functions as a channel selector and indicator. The purpose of our project is to give the best from our project for consumer to use the advantages of our project. To control this digital switching system, we use push to-on switch. SI for reset, S2 for count up and S# for count down. Our project can apply in industrial and for safety system. For example, we can use it as a gate to make sure that area is safety. It also to avoid any unpleasant incident from occurs. Another application of our project is function like a channel selector for TV or radio.